Analysis of Farmers’ Crop Rotation Intention and Behavior Using Structural Equation Modeling: Evidence from Heilongjiang Province, China - Rui Zhang; Guoming Du; Bonoua Faye; Haijiao Liu (Land)
Exploring the factors driving farmers’ crop rotation intention and behavior can provide a scientific foundation for enhancing crop rotation policies. Utilizing 448 micro-research samples from three counties in Heilongjiang Province, a structural equation model was developed to examine the factors influencing farmers’ crop rotation intention and behavior. This analysis focused on farmer cognition, family endowment, and the external environment. The study results indicate that farmer cognition and family endowment positively impact their intention to rotate. The rotation intention, in turn, is a crucial driver of actual rotation behavior. However, the external environment tends to affect rotational behavior negatively. Then, positive effects were noted, and factors such as the benefits of crop rotation, policy awareness, social support, larger cropland area, narrower return, the profit gap between maize and soybean, lower spatial connectivity standard, and higher crop rotation subsidy standard significantly encourage farmers’ crop rotation intention and behavior. In a nutshell, to effectively promote the area of rotation, it is crucial to enhance policy communication, target subsidy to larger households, and establish differentiated subsidy standards. These measures are essential to boosting farmers’ motivation and increasing the adoption of crop rotation in the region.